2018
DOI: 10.17140/csmmoj-4-125
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Spectrum of Early Life Exposure-Related Inflammation and Epigenetic Therapy

Abstract: Early life exposure to a variety of insults during sensitive windows of development can reprogram normal physiological responses and alter disease susceptibility later in life. During this process, Inflammation triggered by a variety of adverse exposures plays an important role in the initiation and development of many types of diseases including tumorigenesis. This review article summaries the current knowledge about the role and mechanism of inflammation in development of diseases. In addition, epigenome alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…On the other hand, protective factors for uterine fibroids include combined oral contraception or injectable medroxyprogesterone acetate in the depot form, smoking in women of low mass, and parity ( 1 ). Other important risk factors include obesity ( 23-25 ), vitamin D deficiency ( 26-28 ), excessive vitamin E levels ( 29 ), altered reproductive tract microbiome ( 30 ), exposure to endocrine-disrupting chemicals (eg, organophosphate esters and plasticizers) ( 31 , 32 ), and various early-life adverse environmental exposures ( 33 ). Individual and environmental risk factors associated with tobacco smoking and alcohol abuse can also contribute to the formation of uterine fibroids ( 34 , 35 ).…”
Section: Epidemiology Risk/protective Factors Driver Mutations and Tu...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, protective factors for uterine fibroids include combined oral contraception or injectable medroxyprogesterone acetate in the depot form, smoking in women of low mass, and parity ( 1 ). Other important risk factors include obesity ( 23-25 ), vitamin D deficiency ( 26-28 ), excessive vitamin E levels ( 29 ), altered reproductive tract microbiome ( 30 ), exposure to endocrine-disrupting chemicals (eg, organophosphate esters and plasticizers) ( 31 , 32 ), and various early-life adverse environmental exposures ( 33 ). Individual and environmental risk factors associated with tobacco smoking and alcohol abuse can also contribute to the formation of uterine fibroids ( 34 , 35 ).…”
Section: Epidemiology Risk/protective Factors Driver Mutations and Tu...mentioning
confidence: 99%
“…The immune cells and secreted cytokines and chemokines may influence uterine fibroid development and the tumor microenvironment. The myometrial and systemic immune profiles of women with fibroids should be investigated better to understand the role of inflammation linking to epigenome ( 33 ) in uterine fibroid pathogenesis.…”
Section: Key Pathways Contributing To Uterine Fibroids Formationmentioning
confidence: 99%
“…[ 4 , 5 ] A previous in vitro study [ 6 ] suggested that progenitor cells of uterine leiomyoma promote the development of uterine leiomyoma through the expression of related inflammatory factors. Current studies on uterine leiomyoma and inflammation [ 7 , 8 ] focus on inflammatory factors such as interleukin-4 (IL-4), IL-5, IL-10, and IL-13, and evidence regarding the relationship between neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) in patients with uterine leiomyomas is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In case of UFs, inflammation switches mostly to immunosuppression due to tumor evasion from anti-tumor immune response. However, in many cases this pathway is still unknown and hard to describe in detail [35]. Early life and prenatal exposure to different stimuli increase the risk of diseases in later life, due to the inflammation-derived reprogramming of the epigenome.…”
mentioning
confidence: 99%
“…Early life and prenatal exposure to different stimuli increase the risk of diseases in later life, due to the inflammation-derived reprogramming of the epigenome. It is frequently one the main causes of UF occurrence [35]. Paracrine signaling plays an important role in the cellular transformation of the myometrium.…”
mentioning
confidence: 99%